2018
DOI: 10.1002/jaba.478
|View full text |Cite
|
Sign up to set email alerts
|

Teaching preschool children to report suspicious packages to adults

Abstract: Law enforcement agencies stress that public reporting of terror-related crime is the predominant means for disrupting these actions. However, schools may be unprepared because the majority of the populace may not understand the threat of suspicious materials or what to do when they are found on school grounds. The purpose of this study was to systematically teach preschool children to identify and report suspicious packages across three experiments. In the first experiment, we used multiple exemplar training t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Behavior‐analytic research has demonstrated that teaching children safety skills may be an effective way to keep them safe from potentially dangerous stimuli (Jones et al, 1981; May et al, 2018). One evidence‐based intervention used to teach a variety of safety skills to individuals is behavioral skills training (BST; Giannakakos et al, 2018; Ledbetter‐Cho et al, 2016; Nabeyama & Sturmey, 2010; Parsons et al, 2012; Quintero et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Behavior‐analytic research has demonstrated that teaching children safety skills may be an effective way to keep them safe from potentially dangerous stimuli (Jones et al, 1981; May et al, 2018). One evidence‐based intervention used to teach a variety of safety skills to individuals is behavioral skills training (BST; Giannakakos et al, 2018; Ledbetter‐Cho et al, 2016; Nabeyama & Sturmey, 2010; Parsons et al, 2012; Quintero et al, 2019).…”
mentioning
confidence: 99%
“…Behavioral skills training involves instructions, modeling, rehearsal, and feedback in which teaching continues until the trainee acquires the skill and demonstrates that they can perform it independently (Miltenberger, 2008). Behavioral skills training has been used to teach a number of safety responses in the presence of dangerous stimuli, such as firearms (Rossi et al, 2017), abduction lures (Ledbetter‐Cho et al, 2016), suspicious packages (May et al, 2018), school safety threats (Dickson & Vargo, 2017), and potential poisons (Summers et al, 2011). In situ training (IST) has been used along with BST and involves assessing whether the target skill occurs in a naturalistic setting.…”
mentioning
confidence: 99%